Valorization of Food Waste to Produce Eco-Friendly Means of Corrosion Protection and “Green” Synthesis of Nanoparticles - Georgii Vasyliev; Victoria Vorobyova (Advances in Materials Science and Engineering)
Agrifood by-products are a key element within Europe’s sustainable strategies. Valorization and reuse of zero-waste technologies are becoming more popular, and they are commonly named as “second-generation food waste management.” The present study is directed to the valuable extracts of “green” organic compounds from the by-products of fruit and berry/vegetable crops, which can be revalorized in sustainable chemical technology and engineering, namely, in the production of “green” synthesis of nanoparticles and for the inhibition of corrosion and scaling of metals in corrosive media. Numerous types of agrifood by-products (rapeseed pomace, sugar beet pulp, fodder radish cake, grape pomace, and pomegranate peels) were investigated. The waste extracts for corrosion and scale inhibitors of mild steel in tap water were prepared by the conventional extraction method that uses 2-propanol and characterized by gas chromatography-mass spectroscopy (GC-MS). Inhibition of scaling and corrosion was investigated in thermal scaling conditions on the surface of the electrode manufactured from mild steel. The LPR technique was applied to measure the corrosion rate, and the scaling rate was determined gravimetrically. The extracts were found to inhibit the corrosion rate 2-3 times, while only radish cake extract inhibited both the corrosion and scaling rates. The waste extracts to produce nanoparticles were prepared by the ultrasound-assisted water extraction with subsequent oxidation by oxygen purge and characterized by liquid chromatography-mass spectroscopy (LC-MS). The aqueous grape pomace and pomegranate peel extracts were screened for total phenolic content (TPC) and total flavonoid content (TFC). The reduction capacity of the extracts was assessed using ferric reducing power (FRAP) and phosphomolybdenum (PM) assays. AgNPs were characterized by UV-Vis spectroscopy, dynamic light scattering (DLS), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscope (SEM), and energy-dispersive X-ray spectroscopy (EDX) analysis. The particle size of AgNPs ranged between 40 and 50 nm. The antimicrobial activity of AgNPs was tested against Escherichia coli using the agar diffusion method and optical density.